Peningkatan Kinerja Guru Kelas I, II, dan III dalam Menyusun Perangkat Administrasi Kelas Melalui Kegiatan Supervisi Administrasi Di MIN 2 Kota Pasuruan - Siti Maryam (Jurnal Simki Postgraduate, 2023)
The background of this research is that many teachers encounter learning problems, Madrasah heads have not carried out supervision tasks effectively and continuously in an effort to improve teacher performance. The formulation of the problem in this study is how can the implementation of classroom teacher administrative supervision improve the performance of class I, II and III teachers at MIN 2 Pasuruan City? The aims of this study were to: (1) determine the effectiveness, impact and implementation model of class teacher administration supervision at MIN 2 Pasuruan City towards improving the performance of class I, II and III teachers in preparing class teacher administration. The subjects in the study were 3 teachers at MIN 2 Pasuruan City. The data collection techniques used were interviews, observation and documentation analysis. The validity of the data used is the technique of triangulation of sources and methods. Based on the results of the study, it can be concluded that the increase in teacher performance in preparing class administration, where in the initial conditions there were no teachers who were able to properly arrange class administration, this was evidenced by the low average score obtained by teachers, namely 78 and only entering in the less category, in the first cycle it increased quite significantly even though there were still no teachers who were declared able to organize class administration properly, by obtaining an average classical value of 118 and included in the sufficient criteria and in the last cycle being a teacher or 100%, it was proven with the acquisition of a classical value of 158 in the criteria of good value. The conclusion is that supervision of class teacher administration carried out by the head of the Madrasah for 3 teachers at MIN 2 Pasuruan City was declared successful in improving teacher performance in preparing class teacher administration.